Individual differences in behavior affect total tract fiber digestibility: the example of collared peccary - R.M. Borges; S.L.G. Nogueira-Filho; P.L.G. Cairo; S.S.C. Nogueira; A. Mendes; L.G. Aldrigui; M. Vandenheede; J. Bindelle (Animal, 2020)
Differences in how individuals cope with stressful conditions (e.g. novel/unfamiliar environment, social isolation and increases in human contact) can explain the variability in data collection from nutrient digestibility trials. We used the collared peccary (Pecari tajacu), which is under process of domestication and shows high individual behavioral distinctiveness in reactions toward humans, to test the hypothesis that behavioral differences play a role in nutrient digestibility. We assessed the individual behavioral traits of 24 adult male collared peccaries using both the ‘behavioral coding’ and the ‘subjective ratings’ approaches. For the behavioral coding assessment, we recorded the hourly frequency of behaviors potentially indicative of stress during the 30-day habituation period to the experimental housing conditions. The subjective ratings were performed based on the individuals’ reactions to three short-term challenge tests (novel environment, novel object and threat from a capture net) over a period of 56 days. During the last 26 days, the collared peccaries were fed diets either high (n = 12) or low (n = 12) in dietary fiber levels, and we determined the total tract apparent digestibility of nutrients. The individual subjective ratings showed consistency in the correlated measures of ‘relaxedness’, ‘quietness’ and ‘satisfaction’ across the three challenge tests, which were combined to produce z score ratings of one derived variable (‘calmness’). Individual frequency of BPIS/h and calmness scores were negatively correlated and both predicted the total tract digestibility of acid detergent fiber (ADF), which ranged from 0.41 to 0.79. The greater the calmness z scores (i.e. calmer individuals), the greater the total tract digestibility of ADF. In contrast, the higher the frequency of BPIS/h, the lower the total tract digestibility of ADF. Therefore, our results provide evidence that by selecting calmer collared peccaries, there will be an increase in their capacity to digest dietary fiber.